2008
DOI: 10.1007/s00221-007-1246-z
|View full text |Cite
|
Sign up to set email alerts
|

Hand digit control in children: motor overflow in multi-finger pressing force vector space during maximum voluntary force production

Abstract: The aim of this study was to investigate the contralateral motor overflow in children during single-finger and multi-finger maximum force production tasks. Forty-five right handed children, 5-11 years of age produced maximum isometric pressing force in flexion or extension with single fingers or all four fingers of their right hand. The forces produced by individual fingers of the right and left hands were recorded and analyzed in four-dimensional finger force vector space. The results showed that increases in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…Therefore, it is thought that mirror movements occur in young children because of the immaturity of the corpus callosum, which fails to inhibit the ipsilateral motor projections or motor overflow from the active motor cortex to the nonactive motor cortex [45, 49, 50]. A developmental trend has been shown in which mirror movements decrease significantly until 6–8 years of age, which is the age range at which the myelination of the corpus callosum occurs [43, 50]. …”
Section: Nonpathological Factors Can Influence Motor Interhemisphementioning
confidence: 99%
“…Therefore, it is thought that mirror movements occur in young children because of the immaturity of the corpus callosum, which fails to inhibit the ipsilateral motor projections or motor overflow from the active motor cortex to the nonactive motor cortex [45, 49, 50]. A developmental trend has been shown in which mirror movements decrease significantly until 6–8 years of age, which is the age range at which the myelination of the corpus callosum occurs [43, 50]. …”
Section: Nonpathological Factors Can Influence Motor Interhemisphementioning
confidence: 99%
“…In adult, associated movement is regarded as a pathological phenomenon (Connolly and Stratton, 1968). However, normally developing children and adolescents can represent the associated movements to a various degree depending on the motor task, development of the corpus callosum and maturation of motor control network (Mayston et al, 1999; Hoy et al, 2004; Shim et al, 2008; Koerte et al, 2009; Gasser et al, 2010; Qiu et al, 2010). On the other hand, decrement of IHI following brain injury is a basic mechanism of the contribution of the unaffected motor cortex, which has been regarded as a mechanism for motor recovery (Liepert et al, 2000; Manganotti et al, 2002; Shimizu et al, 2002; Jang et al, 2009; Jang, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In studies on bimanual coordination in children, a commonly observed phenomenon is unintentional motor "overflow," in which an intentional movement is accompanied by sympathetic movement of associated muscles, for example, in the opposite hand (Parlow, 1990). This motor overflow between the mirroring limbs on the left and right side of the body decreases as a function of age (Shim et al, 2008), similarly to the decrease of enslaving effects between different fingers of the left hand as discussed earlier in this paper (Shim et al, 2007). When the task-performing hand is the nondominant left hand, the sympathetic movement in the other hand is most significant.…”
Section: Effects Of Overflow On Bimanual Coordinationmentioning
confidence: 99%